APPLICATION OF RESTORATIVE JUSTICE IN NARCOTICS CRIME CASES BY MOJOKERTO CITY NATIONAL NARCOTICS AGENCY - M. Khoirul Anam; Pudji Astuti (Universitas Negeri Surabaya, 2023)
Abstract Narcotics addicts in Mojokerto from 2016 to mid-2022 there were 257 clients. In 2019, there were 33 addicts, and in 2020 there were 38 addicts. During 2021 there were 50 people then by mid-year of 2022, there were 42 addicts. This case has impacted the overcapacity of Correctional Institutions in prisons in Mojokerto. One effort that had be done is to use a restorative justice approach. This study aims to identify and explain the application of restorative justice in cases of narcotics crimes by the Mojokerto BNN, to identify and describe the supporting and inhibiting factors for implementing restorative justice in tackling narcotics crimes by the Mojokerto BNN. The results of this study indicate that the BNN in Mojokerto has never succeeded in implementing restorative justice in cases of narcotics crimes because it only handles cases with suspects as dealers. There are five supporting factors while implementing restorative justice in narcotics crime cases at BNN Mojokerto, regulations, and law enforcement have been formed, facilities and infrastructure have also been fulfilled, increasing public knowledge of settlements through restorative justice. As well as there are two main factors inhibiting the application of restorative justice in narcotics crime cases at the BNN in Mojokerto. These two supporting factors are at the same time hindering its implementation, the rules regarding the implementation of restorative justice which have a limited period, and the absence of team members in the integrated assessment that are not represented by other officers. Keywords: Mojokerto National Narcotics Agency, Restorative Justice, Narcotics Crime, Actors.